1991
DOI: 10.1152/ajpheart.1991.261.3.h611
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of positive inotropic effect of endothelin on mammalian ventricular myocardium

Abstract: Endothelin-1 elicited a positive inotropic effect (PIE) on isolated rabbit, guinea pig, and rat but not on dog ventricular myocardium. Specific high-affinity binding of 125I-labeled endothelin-1 was detected in the ventricular membrane fraction of these species. Maximal binding capacity was the highest in the rabbit, lowest in the dog, and in between in the guinea pig and rat; this rank order corresponds roughly to the effectiveness of endothelin-1 in producing a PIE. There was no difference in the potency or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
66
1
3

Year Published

1993
1993
1996
1996

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 0 publications
8
66
1
3
Order By: Relevance
“…However, ET-1 did not cause positive inotropic affects in six strips obtained from the human ventricle strip that responded normally to (-)-isoprenaline (Davenport et al 1989) and caused only very small inotropic effects in another study (Moravec et al 1989). In this respect, it is of interest that the receptor density in the ventricle of several animal species has previously been found to correspond to the effectiveness of ET-1 in producing a positive inotropic effect (Takanashi and Endoh 1991). Functionally differential effects on human atrial and ventricular tissue have also been observed for 5-hydroxytryptamine which produced a positive inotropic effect on the isolated atrium (Kaumann et al 1991) which could not be shown in the ventricle (Jahnel et al 1992;Schoemaker et al 1992a, b).…”
Section: Endothelin Receptors In the Ventricle And The Atriummentioning
confidence: 96%
See 3 more Smart Citations
“…However, ET-1 did not cause positive inotropic affects in six strips obtained from the human ventricle strip that responded normally to (-)-isoprenaline (Davenport et al 1989) and caused only very small inotropic effects in another study (Moravec et al 1989). In this respect, it is of interest that the receptor density in the ventricle of several animal species has previously been found to correspond to the effectiveness of ET-1 in producing a positive inotropic effect (Takanashi and Endoh 1991). Functionally differential effects on human atrial and ventricular tissue have also been observed for 5-hydroxytryptamine which produced a positive inotropic effect on the isolated atrium (Kaumann et al 1991) which could not be shown in the ventricle (Jahnel et al 1992;Schoemaker et al 1992a, b).…”
Section: Endothelin Receptors In the Ventricle And The Atriummentioning
confidence: 96%
“…In the rabbit isolated papillary muscle, the positive inotropic response appeared to be mediated by the ET B receptor (Takanashi and Endoh 1991), but the nature of the receptor involved in endothelin-induced rat myocyte hypertrophy and secretion of natriuretic peptide from rat myocytes (Shubeita et al 1990) thus far remains unknown. The human ventricle has recently been shown to contain both ET A and ETB receptors, e.g.…”
Section: Endothelin Receptors In the Ventricle And The Atriummentioning
confidence: 99%
See 2 more Smart Citations
“…The in vitro positive inotropic effect on human cardiac muscle strips was observed on both atrial and ventricular muscle (Schomisch Moravec et al, 1989). The myocardial contractile actions of ET-1 have also been described in rat and rabbit papillary muscles (Li et al, 1991), and the positive inotropic effect of ET-l was characterized on rabbit, guinea-pig and rat isolated ventricular myocardium (Takanashi & Endoh, 1991).…”
Section: Introductionmentioning
confidence: 97%